1998
DOI: 10.1161/01.hyp.31.1.139
|View full text |Cite
|
Sign up to set email alerts
|

Venous Tone in the Developmental Stages of Spontaneous Hypertension

Abstract: Abstract-The initial stages of hypertension in the spontaneously hypertensive rat (SHR) are characterized by an increase in cardiac output. Venous capacitance plays an important role in the control of cardiac output. This study tested the hypothesis that venous tone is elevated in the developmental stages of spontaneous hypertension. Male SHR or normotensive Wistar-Kyoto (WKY) rats were instrumented for the measurement of arterial pressure (FAP) and intrathoracic vena caval pressure (FVP). A latex-tipped cathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
36
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 32 publications
8
36
0
3
Order By: Relevance
“…These findings are in agreement with published data that ET-1 produces O 2 Ϫ via its ET A receptors in rebound pulmonary hypertension 23 and that the O 2 Ϫ scavenger tempol reduces blood pressure in Ang II-induced hypertensive rats. 2,4 More important, those studies also concur with our recent investigations demonstrating the presence of an intact and sustained ET-1-induced venoconstriction mediated by ET A (but not ET B ) receptors in DOCA-salt hypertension. 19 The latter findings argue for a shift in the balance of ET-1-induced contractions that predominate in veins versus arteries in this model, which might contribute to a rise in blood pressure by increasing cardiac output and shifting blood to the arteries.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings are in agreement with published data that ET-1 produces O 2 Ϫ via its ET A receptors in rebound pulmonary hypertension 23 and that the O 2 Ϫ scavenger tempol reduces blood pressure in Ang II-induced hypertensive rats. 2,4 More important, those studies also concur with our recent investigations demonstrating the presence of an intact and sustained ET-1-induced venoconstriction mediated by ET A (but not ET B ) receptors in DOCA-salt hypertension. 19 The latter findings argue for a shift in the balance of ET-1-induced contractions that predominate in veins versus arteries in this model, which might contribute to a rise in blood pressure by increasing cardiac output and shifting blood to the arteries.…”
Section: Discussionsupporting
confidence: 89%
“…The increased sympathetic nerve activity results in augmented venoconstriction, which predominates in the development of spontaneous hypertension. 4 Various humoral factors, such as angiotensin II (Ang II) and ET-1, also induce venoconstriction. 7 Ang II causes impaired arterial NO-mediated relaxation by increasing O 2 Ϫ in Ang II-induced hypertensive rats.…”
mentioning
confidence: 99%
“…1,2 In particular, it has been proposed that attenuated venous elasticity and capacity affect blood volume redistribution in such a manner that blood volume moves from peripheral veins into small arteries 3 or centrally, 2,4 contributing to chronic increases in arterial blood pressure (BP). Supporting this conceptual scheme, previous studies found reduced venous distensibility and blood holding capacity in animals 5,6 and humans [7][8][9] with hypertension. These changes in venous circulation are potentially due to chronic increases in sympathetic autonomic regulation of venous tone.…”
Section: Introductionsupporting
confidence: 56%
“…These changes in venous circulation are potentially due to chronic increases in sympathetic autonomic regulation of venous tone. 6 In addition to chronic influences on vascular tone, the sympathetic nervous system modulates cardiovascular adjustments to short-term physiological perturbations, ensuring blood pressure homeostasis and preserving blood flow. Yet, animals and humans with hypertension often present with altered autonomic modulation and, as a result, they exhibit abnormal cardiovascular responses to short-term physiological stressors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation